2012
DOI: 10.1002/cncr.27673
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of pain variability and its correlates in ambulatory patients with advanced stage cancer

Abstract: BACKGROUND: Although pain is common among patients with advanced cancer, little is known about longitudinal variability in pain intensity. For this report, the authors examined variability in pain intensity over 24 months among ambulatory patients with advanced stage cancers, associations between patient characteristics and within‐patient pain variability, and the relation of pain variability to overall survival. METHODS: The sample comprised 949 patients with solid tumors who received care and reported pain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Those beliefs included ideas such as "Blacks' skin is thicker than Whites" and "Blacks' nerve endings are less sensitive than Whites." Other studies have shown that African American cancer survivors tend to have more daily pain than White survivors [34][35][36][37]. Our findings and previous studies seem to indicate that the medical community may not be addressing pain in non-White patients with cancer as well as White patients.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Those beliefs included ideas such as "Blacks' skin is thicker than Whites" and "Blacks' nerve endings are less sensitive than Whites." Other studies have shown that African American cancer survivors tend to have more daily pain than White survivors [34][35][36][37]. Our findings and previous studies seem to indicate that the medical community may not be addressing pain in non-White patients with cancer as well as White patients.…”
Section: Discussioncontrasting
confidence: 57%
“…As recently as 2016, a study involving medical students and residents revealed that approximately 50 percent of participants had at least one false belief about White patients compared to African American patients [ 33 ]. Those beliefs included ideas such as “Blacks’ skin is thicker than Whites” and “Blacks’ nerve endings are less sensitive than Whites.” Other studies have shown that African American cancer survivors tend to have more daily pain than White survivors [ 34 , 35 , 36 , 37 ]. Our findings and previous studies seem to indicate that the medical community may not be addressing pain in non-White patients with cancer as well as White patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pain variability is an increasingly recognized phenomenon. 9 Changes in pain severity over time predict disability of patients with cancer. 10 The economic costs of chronic pain are enormous, 11 as are its' effects on patient function and quality of life (QOL) of patients and their families.…”
Section: Introductionmentioning
confidence: 99%